Students’ Strategies in Translating English Idioms into Bahasa Indonesia of English Language Education - Nadilla Ariyani; Rina Listia; Elvina Arapah (English Department of Faculty of Tarbiyah and Teacher Training, 2021)
Some people find it hard to find the equivalent meaning of English idioms to the target language. This might be caused by their culture and different terms. This study aims to describe the strategies that students use in translating the English idioms into Bahasa Indonesia. The researchers used descriptive qualitative research, and the subjects of this research were 50 students batch 2017 of English Department Universitas Lambung Mangkurat in translation class. The instruments to collect the data were a test and a questionnaire. The data analysis applied was descriptive analysis which involves organize it, divide it into manageable units, and summarize it. The findings showed that the students used four strategies. First, they used idioms of similar meaning and form strategies. Second, students translated using the idioms of similar meaning, but dissimilar form strategies. Students who don’t know the same idioms from the SL used the third strategy, translation by paraphrase to see the entire context and paraphrase to find the meaning, change the idiom to non-idiom is easier to understand the meaning. The last strategy is translation by omission, if paraphrasing idioms is difficult then students will be omitted the entire idioms or sentences.